2019
DOI: 10.1089/sur.2018.272
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Pediatric Cardiac Surgery: Where Are We and Where Do We Go? A Systematic Review

Abstract: Background: Prophylactic antibiotic therapy is given routinely in the peri-operative period to prevent surgical site infection. However, in pediatric cardiac surgery, an optimal schedule has not been defined. Pediatric recommendations follow the guidelines for adults, which might be improper because of the inherent challenges in pediatric research and the heterogeneity of the population. Implementation of an effective prophylaxis protocol is needed for children undergoing cardiac surgery, especially in view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
15
0
7
Order By: Relevance
“…It is evident that acquired infection during ECMO leads to worse clinical outcomes [28]. Notwithstanding, individual infection prevention policies are adopted according to institutional preference [29,30]. Most of the represented strategies used CHG disinfection only for the cannula insertion sites [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that acquired infection during ECMO leads to worse clinical outcomes [28]. Notwithstanding, individual infection prevention policies are adopted according to institutional preference [29,30]. Most of the represented strategies used CHG disinfection only for the cannula insertion sites [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antibiotic pharmacokinetics in paediatric patients undergoing cardiopulmonary bypass (CPB) is not fully known. 20 A suggested schedule has been proposed covering preoperative nasal swab screening and treatment of Staphylococcus aureus with Mupirocin, intraoperative prophylaxis with cefazolin with vancomycin added if MRSA colonisation is present, and continuation of antibiotics for 48 hours postoperatively (prolonged if delayed sternal closure or ECMO or VAD). However, more research is needed to determine and investigate an optimal protocol.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…28 What is helpful with this cefuroxime study by Gertler and colleagues, 28 is that it supports findings from an earlier pharmacokinetic study in older children undergoing cardiovascular surgery in which a similar dosing strategy was found to be appropriate. 29 The review by Jaworski and colleagues 24 is helpful because it highlights the need for prospective randomized trials in children to help establish the correct dose and dosing schedule of antibiotics to assess the efficacy and safety of SAP in pediatric cardiac surgery. This comes at an important time as the United Kingdom's Sixth National Audit on Anesthesia, Surgery, and Life Threatening Allergic Reactions was published in May 2018.…”
Section: Antibiotic Prophylaxis In Pediatric Cardiac Surgerymentioning
confidence: 99%
“…There does not appear to be any randomized trials on the use of surgical antibiotic prophylaxis (SAP) in pediatric cardiac surgery. A recent systematic review of the literature by Jaworski and colleagues 24 identified 20 articles that described the use of perioperative SAP in pediatric cardiac surgery. The use of SAP is very variable.…”
Section: The Cardiac Operating Roommentioning
confidence: 99%
See 1 more Smart Citation